The Influence of Omnichannel Integration on Customer Loyalty through Customer Journey Experience in Modern Retail - Inten Pertiwi; Gede Yudha Anugerah Pratama; A.A. Bagus Bayu Joni Saputra; Renildis Verawati; Juniar Elisabeth Tanda Kawi (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines the role of omnichannel integration in fostering customer loyalty through customer journey experience in Denpasar's fashion retail sector. Using a quantitative explanatory design, data from 200 consumers were analyzed with PLS-SEM. The results reveal that omnichannel integration significantly enhances customer journey experience and customer loyalty. Customer journey experience also positively influences loyalty and partially mediates the relationship between omnichannel integration and loyalty. However, the modest explanatory power of omnichannel integration on customer journey experience indicates that experience formation is shaped by broader contextual and interactional factors. These findings suggest that while channel integration improves consistency across touchpoints, customer loyalty ultimately depends on delivering high-quality experiences throughout the entire customer journey in omnichannel retail environments.